High Sensitivity Troponin (at 0 & 2 Hrs) in Emergency Department. Will Reducing the Interval Time, Safely Reduce Admissions and Costs? - Tahir, Imran (Cardiology and Cardiovascular Medicine, 2017)
Background: Every four minutes someone is admitted to hospital suffering from a heart attack or a chest pain event in the UK, totalling over 150,000 hospitalisations a year. Chest pain is one of the most common presentations in the emergency department and quite a few of them get admitted as low risk ACS patients. With the developments in technology, we have increasingly sensitive troponin assays available. Previous-generation troponin assays have been used as diagnostic and prognostic markers in acute coronary syndrome patients and for risk stratification to guide triage decisions and aid in treatment selection. New, high-sensitivity troponin assays represent an important advance with added sensitivity for cardiac myocyte necrosis. High-sensitivity troponin assays detect concentrations of the same proteins that conventional sensitivity assays are aimed at detecting, just in much lower concentrations. Objective: Can high sensitivity troponin avoid unnecessary admission and save money. Methods: We did the retrospective data analysis for 300 patients presenting in the emergency department of University hospitals Birmingham in January to March 2016. All adult patients admitted with the diagnosis of suspected ACS were included in the study. Results: We included 300 patients admitted with the diagnosis of suspected ACS under the medical team. 81% patients had a serial troponin done during the admission. Rest of the 19% had a single troponin done. Only 10.3% patients had a raise in the serial troponin, rest of them were discharged home. The average length of stay was 33 hours. Conclusion: We have 5-10 patients every day presenting to the emergency department with chest pain. About 50% of them get admitted with the diagnosis of suspected ACS. 81% of our patients could have been potentially disch